Leaving ebook A novel. - Robinson, Roxana (2024)
"Wondrous.... This insightful, complex story about a late-in-life romance is unforgettable." —Joan Frank, The Washington Post What risks would you be willing to take to fall in love again? "I never thought I'd see you here," Sarah says. Then she adds, "But I never thought I'd see you anywhere." Sarah and Warren's college love story ended in a single moment. Decades later, when a chance meeting brings them together, a passion ignites threatening the foundations of their lives. Since they parted in college, each has married, raised a family, and made a career. When they meet again, Sarah is divorced and living outside New York, while Warren is still married and living in Boston. Seeing Warren sparks an awakening in Sarah, who feels emotionally alive for the first time in decades. Still, she hesitates to reclaim a chance at love after her painful divorce and years of framing her life around her children and her work. Warren has no such reservations: he wants to leave his marriage but fears how his wife and daughter will react. As their affair intensifies, Sarah and Warren must confront the moral responsibilities of their love for their families and each other. An engrossing exploration of the vows we make to one another, the tensile relationships between parents and their children, and what we owe to others and ourselves, "Leaving is a tour de force—unfailingly clear-eyed, and its final impact shatters." (Washington Post)